Cambodia : Country Procurement Assessment Report - World Bank (Washington, DC, 2013)
This Country Procurement Assessment Report (CPAR), prepared by the Bank in close cooperation with the Asian Development Bank (ADB), is a contribution to the Government's ongoing public sector reform program. It analyses strengths, and weaknesses in current practices, and outlines an action plan to bring public procurement further into line with internationally accepted, best practice. With regard to public procurement, Cambodia received technical assistance from ADB in 1994-1995, resulting in well-drafted legislation, rules and guidelines, designed to create a coordinated, sound procurement framework in line with good international practice. Through a number of executive decisions made over the ensuing years, however, implementation of the framework has deviated. This has resulted in a fragmented approach, without a focal point for overall monitoring, and resulting in considerable decision-making power in the hands of the Ministry of Economy and Finance (MEF). This CPAR focuses on actions that need to be taken to re-assume the direction intended by the framework, for development of a transparent, public procurement environment, with monitoring carried out by a single agency. The report reviews the status of knowledge of procurement procedures, and the harmonization of donor-funded projects, in line with the private sector participation. It assesses fiduciary risks, lessened somewhat since competitive bidding was introduced in stages over the past 18 months. However, the fiduciary risk is still rated high, on account of existing corruption, with low public sector remuneration creating a climate for rent seeking; weaknesses in the existing regulatory framework; the absence of a sovereign procurement law with a single focal point for monitoring and enforcement; the involvement of MEF in the day-to-day procurement process, which duplicates work, and mitigates against the development of procurement expertise in line agencies; and, the loophole in the 1998 BOT (Build-Operate Transfer) Sub-Decree, that has created a virtually closed environment in the awarding of BOT/concession contracts. Recommendations include, as a highest priority, to hold tripartite discussions between the Government, ADB, and the Bank, in order to agree on an Action Plan for implementing the recommendations of the CPAR, as well as identifying sources of funding for the identified activities. Moreover, the 1995 Sub-Decree needs to be quickly strengthened, while a sovereign procurement law should be enacted. The report specifically stipulates the current practice of awarding concession contracts, without competition, and before carrying out feasibility studies, should cease. In line with a comprehensive training program, there should be a progressive move towards establishing a single agency that would monitor, and oversee all public procurement, act as an advisory and resource center, and implement procurement training programs.